Taxa fotossintética de Egeria densa em ambientes aquáticos da Mata Atlântica e da Caatinga - Dantas, Mônica Rafaele (2016)
This study aimed to compare the photosynthetic rates of submerged aquatic macrophyte E. densa in aquatic environments of the Atlantic Forest and Caatinga. The photosynthesis measurements, respiration and physical and chemical characteristics of water were performed in two seasons (winter and summer) for the Atlantic Forest biome and (dry and wet) for the Caatinga biome. The photosynthesis experiments were carried out at the place of occurrence of E. densa using the environment itself water in the two biomes. Incubations were conducted during the illuminated period of the day (from 6 to 17 hours approximately) lasting an hour each incubation. To determine the photosynthesis and respiration rates we used the method of light and dark bottles, based on variations in dissolved oxygen concentrations determined by the Winkler method. The production of the aquatic macrophyte E. densa had significantly higher values in summer and rainy season than in the dry winter period. In the Atlantic Forest phosphorus and temperature were the variables that possessed greater influence in the primary production of Egeria densa and Caatinga biome production of E. densa increased when exposed to higher radiation values, temperature, phosphorus and lower nitrogen values. Photosynthetically active radiation and water temperature are factors that can act together or separately in increasing primary production of macrophytes and may vary according to species and geographical location. Primary production of submerged aquatic macrophyte E. densa was higher in the Caatinga during the rainy season, influenced by higher levels of photosynthetically active radiation and water temperature